Let's solve the equation step by step and fill in the missing terms and descriptions.
Starting from the original equation:
\[ \frac{y}{-16} - 13 = -13 \]
-
Step 1: Add 13 to both sides. \[ \frac{y}{-16} - 13 + 13 = -13 + 13 \] This simplifies to: \[ \frac{y}{-16} = 0 \]
-
Step 2: Now we need to isolate \(y\). To do this, multiply both sides by \(-16\): \[ -16 \cdot \frac{y}{-16} = 0 \cdot -16 \] This simplifies to: \[ y = 0 \]
So, the completed process is:
- Fill in the missing term: \(y = 0\)
- Select the missing description: "Multiply both sides by -16"
Thus, the final answer is:
- \(y = 0\)
- Multiply both sides by \(-16\)